Titanium Implant Surface Effects on Adherent Macrophage Phenotype: A Systematic Review - Pitchai, Manju; Ipe, Deepak; Tadakamadla, Santosh; Hamlet, Stephen (Materials, 2022)
Immunomodulatory biomaterials have the potential to stimulate an immune response able to promote constructive and functional tissue remodeling responses as opposed to persistent inflammation and scar tissue formation. As such, the controlled activation of macrophages and modulation of their phenotype through implant surface modification has emerged as a key therapeutic strategy. Methods: Online databases were searched for in vitro studies between January 1991 and June 2020 which examined the effect of titanium implant surface topography on the adherent macrophage phenotype at either the gene or protein level. Results: Thirty-nine studies were subsequently included for review. Although there was significant heterogeneity between studies, treatment of titanium surfaces increased the surface roughness or hydrophilicity, and hence increased macrophage attachment but decreased cell spreading. Physical coating of the titanium surface also tended to promote the formation of cell clusters. Titanium and titanium-zirconium alloy with a micro- or nano-scale rough topography combined with a hydrophilic surface chemistry were the most effective surfaces for inducing an anti-inflammatory phenotype in adherent macrophages, as indicated by significant changes in cytokine gene expression and or cytokine secretion profiles. Conclusions: The published data support the hypothesis that incorporation of specific topographical and physiochemical surface modifications to titanium can modulate the phenotypic response of adherent macrophages.